1985
DOI: 10.1093/carcin/6.12.1735
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effects of N-acetylcysteine on glutathione metabolism and on the biotransformation of carcinogenic and/or mutagenic compounds

Abstract: N-acetylcysteine (NAC) was administered to rats in various combinations with an enzyme inducer (Aroclor 1254) and with depletors of reduced glutathione (GSH), i.e., diethyl maleate (DEM) and buthionine sulfoximine (BSO). NAC increased intracellular glutathione levels in erythrocytes and in liver and lung cells, and replenished its stores following depletion. It did not affect the concentrations nor the spectral properties of cytochromes P-450 in hepatic and pulmonary microsomes, whereas it stimulated, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(76 citation statements)
references
References 0 publications
3
72
0
1
Order By: Relevance
“…Although the hver may play a significant role in NAC metabolism, several studies including our own have shown that liver GSH levels are not significantly increased following NAC (De Flora et al, 1985;McLellan et al, 1995;Pratt and loaimides, 1985), or oral GSH (Aw, Wierzbicka, and Jones, 1991) administration. NAC is a proven effective countermeasure for liver toxicity as a result of acetaminophen overdose (Corcoran and Wong, 1986;Lauterburg, Corcoran, and Mitchell, 1983) and this has lead to the hypothesis that NAC is chemoprotective because it boosts GSH biosynthesis in the liver.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Although the hver may play a significant role in NAC metabolism, several studies including our own have shown that liver GSH levels are not significantly increased following NAC (De Flora et al, 1985;McLellan et al, 1995;Pratt and loaimides, 1985), or oral GSH (Aw, Wierzbicka, and Jones, 1991) administration. NAC is a proven effective countermeasure for liver toxicity as a result of acetaminophen overdose (Corcoran and Wong, 1986;Lauterburg, Corcoran, and Mitchell, 1983) and this has lead to the hypothesis that NAC is chemoprotective because it boosts GSH biosynthesis in the liver.…”
Section: Discussionmentioning
confidence: 74%
“…Certain forms of cancer, neurodegenerative, and cardiovascular diseases have been linked to GSH depletion (Pastore et al, 2003). NAC supplementation increases GSH levels in humans (De Rosa et al, 2000;Pendyala and Creaven, 1995) and animals (De Flora et al, 1985;Lailey, 1997;McLellan et al, 1995). NAC stimulates glutathione-S-transferase (GST) transcription (Xia et al, 1996), which may contribute to its anti-oxidant properties.…”
Section: Introductionmentioning
confidence: 99%
“…NAC is a precursor of extracellular and intracellular glutathione (GSH) (de Flora et al, 1985;Cotgreave et al, 1986) and it is widely used in the treatment of patients with chronic bronchitis and emphysema. It has become popular for its potent anti-oxidant/de-toxificant properties.…”
Section: Head and Neck And Lung Cancermentioning
confidence: 99%
“…20 It can prevent increased oxidative stress following administration of radiocontrast agents and therefore has become widely used to prevent contrast-induced nephropathy. Meanwhile, Nacetylcysteine supplementation has been shown to be a promising therapy for oxidative stres and related complications including cardiovascular events in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%